Uji Fitokimia Ekstrak Metanol Bunga Tumbuhan Bunga Pagoda (Clerodendrum paniculatum L.) - Teuku Muhamad Khairudin; Sri Benti Etika; Melindra Mulia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Research has been carried out on phytochemical screening on the flowers of the pagoda flower plant (Clerodendrum paniculatum L.). This study aims to determine the content of secondary metabolites in the flowers of the pagoda flower plant. The secondary metabolites tested in this study were alkaloid, flavonoid, steroid, triterpenoid, and saponin. The results showed that the flowers of the pagoda flower plant (Clerodendrum paniculatum L.) contained secondary metabolites, namely alkaloid, flavonoid, and saponin.